Intraoperative conversion during video-assisted thoracoscopy resection for lung cancer does not alter survival. (15th February 2021) - Fourdrain, Alex; Georges, Olivier; Lafitte, Sophie; Meynier, Jonathan; Berna, Pascal
Abstract:  : OBJECTIVES: The aim of this study was to assess the long-term outcomes of patients treated by anatomical pulmonary resection with the video-assisted thoracoscopic surgery (VATS) approach, VATS requiring intraoperative conversion to thoracotomy or an upfront open thoracotomy for lung cancer surgery. METHODS: We performed a retrospective single-centre study that included consecutive patients between January 2011 and December 2018 treated either by VATS (with or without intraoperative conversion) or open thoracotomy for non-small-cell lung cancer (NSCLC). Patients treated for a benign or metastatic condition, stage IV disease, multiple primary lung cancer or by resection, such as pneumonectomies or angioplastic/bronchoplastic/chest wall resections, were excluded. RESULTS: Among 1431 patients, 846 were included: 439 who underwent full-VATS, 94 who underwent VATS-conversion (21 emergent, 73 non-emergent) and 313 treated with upfront open thoracotomy. The median follow-up was 37 months. There were no statistical differences in stage-specific overall survival between the full-VATS, VATS-conversion, and open thoracotomy groups, with 5-year OS for stage I NSCLC of 76%, 72.3% and 69.4%, respectively ( P  = 0.47). There was a difference in disease-free survival for stage I NSCLC, with 71%, 60.2% and 53%, respectively at 5 years ( P  = 0.013). Fewer complications occurred in the full-VATS group (pneumonia, arrhythmia, length of stay), but complication rates were similar between the VATS-conversion and thoracotomy groups. CONCLUSIONS: VATS resection for NSCLC with intraoperative conversion does not appear to alter the long-term oncological outcome relative to full-VATS or open upfront thoracotomy. Postoperative complications were higher than for full-VATS and comparable to those for thoracotomy. VATS should be favoured when possible.